Colonial Discourse and Gender in U.S. Criminal Courts : Cultural Defenses and Prosecutions. - Braunmühl, Caroline (Routledge advances in criminology., 2012)
The occurrence in some criminal cases of ""cultural defenses"" on behalf of ""minority"" defendants has stirred much debate. This book is the first to illuminate how ""cultural evidence""--I.e., ""evidence"" regarding ethnicity - is actually negotiated by attorneys, expert/lay witnesses, and defendants in criminal trials. Caroline Braunmühl demonstrates that this has occurred, overwhelmingly, in ways shaped by colonialist and patriarchal discourses common in the Western world. She argues that the controversy regarding the legitimacy of a ""cultural defense"" has tended to obscure this fact.